2022
DOI: 10.1088/1742-6596/2267/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of nanoparticles on performance of solar stills

Abstract: The necessity of fresh water is growing day by day as the population and industrialization is increasing. As earth contains 71% of salinity water we have to convert that salinity water into fresh drinkable water. The device which converts salty water into drinkable water by using green source of energy that device is known as solar still. But due to its lesser efficiency it cannot be used in industrial purposes. To increase its productivity and efficiency many researcher has done improvement in various stills.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It showed the use of pure nanoparticles and nanoparticles integrated with PCM; which helps in increasing the PCM thermal conductivity when compared to base fluids and has been chosen as the best suitable technique for increasing still productivity. A review paper published in 2021 [27] found that the efficiency and daily productivity of the solar still was increased by using nanoparticles in it. Another review [28] investigated experimentally the impact of combined utilization of copper oxide (CuO) nanoparticles, both in thermal energy storage unit and absorber coating, on the performance of a single-slope solar still.…”
Section: Introductionmentioning
confidence: 99%
“…It showed the use of pure nanoparticles and nanoparticles integrated with PCM; which helps in increasing the PCM thermal conductivity when compared to base fluids and has been chosen as the best suitable technique for increasing still productivity. A review paper published in 2021 [27] found that the efficiency and daily productivity of the solar still was increased by using nanoparticles in it. Another review [28] investigated experimentally the impact of combined utilization of copper oxide (CuO) nanoparticles, both in thermal energy storage unit and absorber coating, on the performance of a single-slope solar still.…”
Section: Introductionmentioning
confidence: 99%